Camões y Lucano - Vieira, Brunno Vinicius Gonçalves [UNESP] (My University, 2010)
Camoens, the great Portuguese epic, was a Lucan’s reader, although it seems forgotten by some critics. Among the ancient writers who have influenced Camoens’ text, the Latin poet Lucan (AD 65) receives a smaller, but not irrelevant attention. This paper presents some allusions to Lucan in Os Lusíadas of Camoens, specially exploiting a long imitation of Pharsalia, II, 585-595.

Camões, el gran poeta épico portugués, fue lector de Lucano, hecho que parece haber sido olvidado por algunos críticos. Entre los escritores que influenciaron su poema, el poeta latino Lucano recibió menos atención que otros, aunque esto no lo torna menos relevante. Este artículo presenta algunas alusiones a Lucano presentes en Os Lusíadas de Camões, dando especial énfasis a una larga imitación de la Pharsalia, II, 585-595.
Camoens and Lucan
Keywords: Comoens; Lucan; Poetry; Translation; Imitation; Camões; Lucano; Poesía; Traducción; Imitación